Biocomposite Anchors Have Greater Yield Load and Energy Compared With All-Suture Anchors in an In Vitro Ovine Infraspinatus Tendon Repair Model - Robert A. Walton, M.D; Lindsey Liuzza, M.D; Catherine Takawira, M.S; Claudia Leonardi, Ph.D; Mandi J. Lopez, D.V.M., M.S., Ph.D (Elsevier, 2024)
Purpose: To compare tensile fatigue and strength measures of biocomposite and all-suture anchors in an ovine humerus-infraspinatus tendon model of rotator cuff repair. Methods: Infraspinatus tendons on adult ovine humeri were sharply transected at the insertion. One of each pair was assigned randomly for fixation with 2 biocomposite or all-suture anchors. Constructs were tested with 200 cycles of 20 to 70 N tensile load, and gap formation was measured at the incised tendon end every 50 cycles. They were subsequently tested to failure. Outcome measures including fatigue stiffness, hysteresis, creep, and gap formation and tensile stiffness, and yield and failure displacement, load, and energy were compared between anchors. Results: Biocomposite anchors had greater yield load (134.1 ± 6.5 N, P < .01) and energy (228.6 ± 85.7 J, P < .03) than all-suture anchors (104.7 ± 6.5 N, 169.8 ± 85.7 J). Fatigue properties were not different between anchors, but stiffness and gap formation increased and hysteresis and creep decreased significantly with increasing cycle number. Conclusions: Although the yield displacement of both anchors was within the range of clinical failure, the tensile yield load and energy of ovine infraspinatus tendons secured to the humerus with 2 single-loaded all-suture anchors in a single row were significantly lower than those secured with 2 biocomposite anchors in the same configuration. Clinical Relevance: It is important to understand the biomechanical properties for selecting anchors for rotator cuff repair. A direct comparison of fatigue testing followed by failure strength of infraspinatus tendon fixation with all-suture and biocomposite anchors could help guide anchor selection and postoperative mobility recommendations.